CYP4CJ1-mediated gossypol and tannic acid tolerance in Aphis gossypii Glover. (March 2019) - Ma, Kangsheng; Li, Fen; Tang, Qiuling; Liang, Pingzhuo; Liu, Ying; Zhang, Baizhong; Gao, Xiwu
Abstract: Cytochrome P450 monooxygenases play a key role in herbivorous pest adaptation to host plants by the detoxification against plant allelochemicals. A new P450 gene ( CYP4CJ1 ) was identified from Aphis gossypii, which displayed a positive response to plant allelochemicals. The transcript levels of CYP4CJ1 could be significantly induced by both gossypol and tannic acid. Knockdown of CYP4CJ1 increased the sensitivity of A. gossypii to these two plant allelochemicals. These results suggest that CYP4CJ1 could be involved in the tolerance of A. gossypii to some plant allelochemicals. Subsequently, we examined the regulatory mechanism of CYP4CJ1 based on the transcriptional and post-transcriptional level. A promoter region from −1422 to −1166 of CYP4CJ1 was identified, which was an essential plant allelochemical responsive region. In addition, miR-4133-3p was found to participate in the regulation of CYP4CJ1 post-transcriptionally. Our results suggest that the transcript abundance of CYP4CJ1, following the exposure of A. gossypii to gossypol and tannic acid can be attributed to both the transcriptional and post-transcriptional regulation mechanisms. These results are important for understanding the roles of P450s in the plant allelochemical tolerance of A. gossypii . Graphical abstract: Image 1 Highlights: The expression of CYP4CJ1 was significantly induced by gossypol and tannic acid. Silencing of CYP4CJ1 increased sensitivity of A. gossypii to plant allelochemicals. Region from −1422 to −1173 of CYP4CJ1 is a plant allelochemical responsive region. miR-4133-3p regulates the expression of CYP4CJ1 post-transcriptionally.